1997
DOI: 10.1177/0734242x9701500309
|View full text |Cite
|
Sign up to set email alerts
|

Olive-Mill Wastewater Composting: Microbiological Aspects

Abstract: Oxygen consumption, microbial growth, lignin and phenol degradation, urease, protease and nitrogenase activity were determined during the composting of an olivemill wastewaters (OMW)—wheat straw mixture. Oxygen consumption, microbial growth and urease activity were greatly enhanced during the thermophilic phase, reaching their maximum in about three weeks. Casein-hydrolysing protease showed a high initial activity which sharply decreased after 2 weeks. At the end of the thermophilic phase both phenols an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…2E) and control (Fig. 2D), whose interpretation was based on studies of HA extracted from different organic wastes [6,48,49]. The band around 3300 cm −1 was Table 4 Thermogravimetry (TG) and differential thermal analysis (DTA) parameters for the humic-like fraction (HLF) from olive pulp (OP), its effluents EH 2 and ECH 4 and humic acid (HA) from soil after amendment with OP and both effluents after 6 months assigned to vibration of the OH groups in alcohol, phenol or carboxylic groups.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…2E) and control (Fig. 2D), whose interpretation was based on studies of HA extracted from different organic wastes [6,48,49]. The band around 3300 cm −1 was Table 4 Thermogravimetry (TG) and differential thermal analysis (DTA) parameters for the humic-like fraction (HLF) from olive pulp (OP), its effluents EH 2 and ECH 4 and humic acid (HA) from soil after amendment with OP and both effluents after 6 months assigned to vibration of the OH groups in alcohol, phenol or carboxylic groups.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…La production mondiale des résidus liquides est estimée à 8,4 millions de mètres cubes (NEFZAOUI 1987). Au Maroc, la production annuelle des résidus liquides est estimée à 250 000 mètres cubes (IOM 2003(IOM , 2004 Ces problèmes environnementaux sont attribués à la richesse des effluents en matières organiques (GALLI et al, 1997) et en particulier en polyphénols qui sont responsables de l'effet phytotoxique ZENJARI et al, 2006). Ces considérations ont conduit plusieurs chercheurs aux échelles nationale et internationale à trouver des applications pour le traitement et la valorisation des effluents des huileries d'olive : procédés physiques (ACHAK et al, 2008;AL-MALLAH et al, 2000), procédés thermiques (DI GIACOMO et al, 1991;VITOLO et al, 1999), floculation et clarification (FLOURI et al, 1996), adsorption (ACHAK et al, 2009a), compostage (AIT-BADDI et al, 2004PAREDES et al, 2000) et infiltration-percolation (ACHAK et al, 2009b;SAADI et al, 2007;SANTI et al, 2008;SAYADI et al, 2000).…”
Section: Introductionunclassified
“…The OMWW has to be preabsorbed in a solid substrate in order to proceed with the composting process. To obtain good results, a broad variety of bulking agents, including wheat straw (Galli et al 1997;Tomati et al 1995), maize straw (Paredes et al 2000) and solid olive and olive tree waste (Vlyssides et al 1999;Filippi et al 2002), have been found acceptable.…”
Section: Bioremediation Of Olive-mill Waste By Compostingmentioning
confidence: 99%